PENGARUH SUHU KALSINASI PADA SINTESIS Fe-DOPED TITANIUM DIOKSIDA DENGAN METODE SOL-GEL - , FARIDA FITRIAH, Dr. Akhmad Syoufian ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purpose of this research was to examine the influence of temperature variations on Fe-doped titanium dioxide (Fe-TiO2) synthesis by sol-gel method as a model of visible light responsive photocatalyst. Fe-TiO2 synthesis by sol-gel method was deemed better than the Fe-TiO2 synthesis by impregnation method through the reflux process. The Fe-TiO2 by sol-gel method was prepared by mixing Titanium Tetraisopropoxide (TTIP) and ethanol in aquabides and FeCl3·6H2O with the concentration of 2% w/w. The product was dried and calcined at temperature of 300, 400, 500, 600 and 700 °C. As for experiment control, Fe-TiO2 was synthesized by impregnation method through the reflux process. Both of Fe-TiO2 samples were characterized by X-Ray Diffraction, Fourier Transform Infrared (FTIR), and Diffuse Reflectance UV-Vis (DR-UV). The XRD data showed that the Fe-TiO2 synthesized using sol-gel method has a smaller crystal size (17,48 nm) than Fe-TiO2 were synthesized by reflux method (40,14 nm). The result of FTIR analysis of both types of samples showed that Fe was succesfully doped into the TiO2. The result of DR-UV analysis of both of Fe-TiO2 showed an increasing in responsiveness to the visible light. As the whole result it can be concluded that Fe can doped into TiO2 producing Fe- TiO2 as a model of visible light responsive photocatalyst, either by sol-gel method or impregation. The most effective method was the sol-gel method with FeCl3·6H2O as a source of Fe at the calcination temperature of 600 ° C that produced a crystal size of 17.48 nm and Eg value of 2.89 eV.